Silver/graphene oxide composite with high thermal/electrical conductivity and mechanical performance developed through a dual-dispersion medium method - Hegeng Wei; Zexi Zhang; Zebo Li; Linfeng Peng; Guannan Yang; Tianshuo Zhao; Yu Zhang; Guanghan Huang; Chengqiang Cui (Journal of Materials Research and Technology, 2024)
Graphene and its derivatives have excellent thermal conductivity, and are common additives for metal-based nanocomposites. However, the easy aggregation of graphene and metal nanoparticles severely limits uniform mixing, and hinders development and performance improvement of metal/graphene composites. Herein, we developed a dual-dispersion medium method to fabricate a silver–graphene oxide (Ag/GO) composite with high thermal/electrical conductivity and mechanical performance. Through the method, GO and silver particles are dispersed evenly in different media and then fully mixed, thereby GO sheets can be uniformly dispersed and form a network in the matrix of silver particles. By adding a low GO content of 0.2 wt%, the density of the sintered Ag/GO joint increased from 9.0 to 9.5 g/cm3, the shear strength increased from 45.8 to 71.9 MPa, the thermal conductivity increased from 234.2 to 375.2 W/(m·K), and the electrical resistivity reduced from 4.6 to 1.9 μΩ cm. The added GO sheets form a coating layer with good interfacial bonding on the surface of most silver particles and form a uniform network in the Ag matrix. In addition, the added GO sheets reduce the overall thermal expansion coefficient and agglomerate size, thereby improving the sintering density and heat transfer efficiency of the Ag/GO composite. Because of its comprehensive properties, the Ag/GO composite material in this study exhibits good potential as a heat dissipation material for packaging and interconnect applications of high-power-density electronic devices.